Religiosity and tolerance in Christian life - a comparative study between Christianity and Islam - - Jinan Hadi Mahmoud,; Kifah Sabir Rashid, (Islamic Sciences Journal, 2024)
ABSTRACT In Christianity, religiosity means the establishment of a certain bond. The person who wants to be connected to God Almighty we call him religious, and the person who is concerned with issues of religion we call him religious. Some thinkers even consider the atheist thinker who spends his life promoting theories related to religion to be a religious person, but in a negative way and on a level that is contrary to religious religiosity, and the best examples of this are: The atheist Nietzsche, the philosopher who lived in tormented anxiety, was haunted by longing for God and worried about ascending to the highest level, but at the same time he was conflicted by that overwhelming desire to descend into the abyss of nothingness, and thus his philosophy remained tinged with longing for God, as if Nietzsche wished from the bottom of his heart to return to God.